(untitled) (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2026)
This article is devoted to the study of Islamic legal mechanisms for preventing family conflicts in the context of modern legislation of the Republic of Uzbekistan. Based on the analysis of primary sources – the Koran and the Sunnah – within the framework of the Maturidite-Hanafi legal tradition, the rights and obligations of spouses, the principles of resolving family disputes, the institution of mediation, as well as Islamic norms in the field of reproductive health are considered. The correspondence and relationship between the norms of Islamic law and the current legislation of Uzbekistan, including the Law of the Republic of Uzbekistan dated 11.03.2019 No ZRU-528, is revealed. The author substantiates the need to implement the proven norms of Islamic family law in the national legal system in order to reduce the growth in the number of divorces and strengthen the institution of the family.